2012
DOI: 10.1017/s0959270912000251
|View full text |Cite
|
Sign up to set email alerts
|

The European wintering population of Steller’s Eider Polysticta stelleri reassessed

Abstract: SummaryProlonged declines in the number of Steller’s Eider Polysticta stelleri wintering in Europe have raised concerns about the conservation status of the Western Palearctic population. Coordinated helicopter surveys of all known wintering areas in Norway and Russia and ground counts in the Baltic in 2009 found c.27,000 Steller’s Eiders, similar to numbers found during the last such survey in the mid-1990s. However, around 85% of the population now winters in Russia compared to 30–50% then. The reasons for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…This can be observed as an overall increase in winter abundance of waterbirds, because part of the population of some species (mainly diving ducks) that formerly wintered further to the southwest now remain in the Baltic Sea (Pavón-Jordán et al, 2019). Many species show decreasing trends in abundance in the southern parts of their wintering ranges (typically in western and southern Europe) but increases near the northern edge of their distribution, typically the Baltic Sea region (MacLean et al, 2008;Skov et al, 2011;Aarvak et al, 2013;Lehikoinen et al, 2013;Pavón-Jordán et al, 2015;Nilsson and Haas, 2016;Marchowski et al, 2017;Fox et al, 2019). Similar shifts are seen in species that traditionally wintered in the Baltic Sea, but currently show declining wintering numbers there, as part of the population now winters in the White, Barents and Kara seas (Fox et al, 2019).…”
Section: Waterbirdsmentioning
confidence: 99%
“…This can be observed as an overall increase in winter abundance of waterbirds, because part of the population of some species (mainly diving ducks) that formerly wintered further to the southwest now remain in the Baltic Sea (Pavón-Jordán et al, 2019). Many species show decreasing trends in abundance in the southern parts of their wintering ranges (typically in western and southern Europe) but increases near the northern edge of their distribution, typically the Baltic Sea region (MacLean et al, 2008;Skov et al, 2011;Aarvak et al, 2013;Lehikoinen et al, 2013;Pavón-Jordán et al, 2015;Nilsson and Haas, 2016;Marchowski et al, 2017;Fox et al, 2019). Similar shifts are seen in species that traditionally wintered in the Baltic Sea, but currently show declining wintering numbers there, as part of the population now winters in the White, Barents and Kara seas (Fox et al, 2019).…”
Section: Waterbirdsmentioning
confidence: 99%
“…However, as a result of the concern, targeted winter helicopter surveys found that these birds had shifted their wintering distributions from Norwegian and Baltic Sea resorts further north and east into Russian waters, which now support 85% of the flyway population, compared with less than 50% in the 1990s (Aarvak et al . ). Throughout Russian Arctic areas, we lack observers to report the presence/absence of waterbirds in these waters, especially during 24 h of darkness, so we have no understanding of how wintering waterbirds have potentially adapted to the availability of open water in these areas.…”
mentioning
confidence: 97%
“…Miller-Rushing et al 2008, Tryjanowski et al 2005. The decline in the Norwegian Steller's Eider wintering population is most likely caused by an eastward shift in distribution, with a larger share of the population now wintering in Russia (Aarvak et al 2012). The present January count was 15 % lower than the count in 2009 for Norway for the similar count section (holding approx.…”
Section: Discussionmentioning
confidence: 99%
“…The present January count was 15 % lower than the count in 2009 for Norway for the similar count section (holding approx. 75 % of the Norwegian wintering population), and representing 6.7 % of the total European count from that year (Aarvak et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation